Energy harvesting wireless communications - Huang, Chuan, 1983-; Zhou, Sheng; Xu, Jie; Niu, Zhisheng; Zhang, Rui; Cui, Shuguang (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
'Energy Harvesting Wireless Communications offers a review of the most current research as well as the basic concepts, key ideas and powerful tools of energy harvesting wireless communications. Energy harvesting is both renewable and cheap and has the potential for many applications in future wireless communication systems to power transceivers by utilizing environmental energy such as solar, thermal, wind, and kinetic energy. The authors--noted experts in the field--explore the power allocation for point-to-point energy harvesting channels, power allocation for multi-node energy harvesting channels, and cross-layer design for energy harvesting links. In addition, they offer an in-depth examination of energy harvesting network optimization and cover topics such as energy harvesting ad hoc networks, cost aware design for energy harvesting assisted cellular networks, and energy harvesting in next generation cellular networks. Market description: Written for academics, researchers, graduate students, and industry research engineers in electrical, electronic, and computer engineering fields, Energy Harvesting Wireless Communications offers a comprehensive resource to the innovations and technology of energy harvesting wireless communications'--
Chapter 3 Power Allocation for Multi-node Energy Harvesting Channels3.1 Multiple-Access Channels; 3.1.1 System Model; 3.1.2 Problem Formulation; 3.1.3 The Optimal Offline Scheme; 3.1.4 Optimal Sum Power Allocation; 3.1.4.1 Optimal Rate Scheduling; 3.1.5 The Online Scheme; 3.1.5.1 Competitive Analysis; 3.1.5.2 The Greedy Scheme; 3.1.6 Numerical Results; 3.2 Relay Channels; 3.2.1 System Model; 3.2.2 Problem Formulation; 3.2.2.1 Delay-Constrained Case; 3.2.2.2 No-Delay-Constrained Case; 3.2.3 Optimal Solution for the Delay-Constrained Case; 3.2.3.1 Monotonic Power Allocation
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 11, 2019).
Keywords: Energy harvesting; Wireless communication systems -- Power supply; Electronic books